The Effect of Community-Based Intervention on Self-Management of Hypertension Patients - Citra Windani Mambang Sari; Ahmad Yamin; Mochamad Budi Santoso (Universitas Pendidikan Indonesia, 2022)
ABSTRACT Introduction: Hypertension is one of the chronic diseases that can cause complications. Patients need a support system in the management of the disease. One of the ways to prevent hypertension complications is by using self-management. Community involvement is integrated into the program to have a social support system in performing self-management. Objective: This study aimed to determine the effect of a community-based intervention on the self-management of hypertension patients in one district in West Java. Methods: The study method is a quasi-experiment with pre and post-test control group design. The samples consist of 60 respondents taken by using the cluster sampling technique. The subjects were divided into control groups who were given routine treatment from primary health care and intervention groups who were given community visit groups about self-management for four weeks, including health education, counseling, and support. The data were collected using a questionnaire about hypertension self-management sub-variables which consisted of diet, smoking, physical activities, stress management, body weight control, alcohol, blood pressure monitoring, and medication. The data analysis techniques were descriptive and inferential statistics using a t-test. Results: The study results showed that the total score for self-management after the intervention was significantly higher than the total score before the intervention (M= 131,62; SD = 12,9; p=0.02). The intervention group's self-management full scores were considerably higher than the control group in the 4th week (p=0.005). Discussions: Community nurses can do one of the interventions by involving the community and forming hypertension volunteer groups that can act as educators to increase hypertension self-management. ABSTRAK Pendahuluan: Hipertensi merupakan salah satu penyakit kronis yang dapat menimbulkan komplikasi. Pasien membutuhkan sistem pendukung dalam pengelolaan penyakitnya. Salah satu cara untuk mencegah komplikasi hipertensi adalah dengan menggunakan manajemen diri. Keterlibatan masyarakat diintegrasikan ke dalam program untuk memiliki sistem dukungan sosial dalam melakukan manajemen diri. Tujuan: Penelitian ini bertujuan untuk mengetahui pengaruh intervensi berbasis komunitas terhadap manajemen diri pasien hipertensi di salah satu kabupaten di Jawa Barat. Metode: Metode penelitian yang digunakan adalah quasi-experiment dengan pre and post-test control group design. Sampel terdiri dari 60 responden yang diambil dengan menggunakan teknik cluster sampling. Subyek dibagi menjadi kelompok kontrol yang diberikan pengobatan rutin dari pelayanan kesehatan primer dan kelompok intervensi yang diberikan kelompok kunjungan masyarakat tentang manajemen diri selama empat minggu, meliputi pendidikan kesehatan, konseling, dan dukungan. Pengumpulan data dilakukan dengan menggunakan kuesioner tentang subvariabel manajemen diri hipertensi yang terdiri dari diet, merokok, aktivitas fisik, manajemen stres, kontrol berat badan, alkohol, pemantauan tekanan darah, dan obat-obatan. Teknik analisis data yang digunakan adalah statistik deskriptif dan inferensial menggunakan uji-t. Hasil: Hasil penelitian menunjukkan bahwa skor total manajemen diri setelah intervensi secara signifikan lebih tinggi daripada skor total sebelum intervensi (M= 131,62; SD = 12,9; p=0,02). Skor penuh manajemen diri kelompok intervensi jauh lebih tinggi daripada kelompok kontrol pada minggu ke-4 (p=0,005). Diskusi: Perawat komunitas dapat melakukan salah satu intervensi dengan melibatkan masyarakat dan membentuk kelompok relawan hipertensi yang dapat berperan sebagai edukator untuk meningkatkan self-management hipertensi.